How to democratize Europe - Hennette-Vauchez, Stéphanie (Harvard University Press, 2019)
The European Union has long suffered from a lack of democratic accountability. In the past decade, the problem has become particularly acute in the economic management of the Eurozone, the 19 countries of the E.U. that use the Euro (nine members don't). At present, the central institution for management of the Eurozone is the Eurogroup, an informal body led by national finance ministers who report neither to the European Parliament nor to national parliaments but coordinate their activities with the Troika, that is, the European Central Bank, the International Monetary Fund, and the European Council. Critics accuse the Eurogroup both of lack of transparency and of consistently putting the interests of the rich northwest ahead of the interests of poorer and smaller nations in the east and south. In How to Democratize Europe, four distinguished French scholars describe the diverse problems of the Eurozone and propose a treaty that would establish a parliament for economic policy consisting of selected members of national parliaments. Various contributors then respond to the proposal with support, criticism, or ideas for alternatives.--